2023
DOI: 10.1186/s12974-023-02715-y
|View full text |Cite
|
Sign up to set email alerts
|

Morinda officinalis oligosaccharides mitigate depression-like behaviors in hypertension rats by regulating Mfn2-mediated mitophagy

Abstract: Objective Patients with hypertension have a risk of depression. Morinda officinalis oligosaccharides (MOOs) have anti-depressant properties. In this study, we aimed to determine whether MOOs can improve the symptoms of depression in individuals with hypertension. Methods Dahl salt-sensitive rats fed with a high-salt diet were stimulated by chronic unpredictable mild stress to mimic hypertension with depression. Primary astrocytes and neurons were i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 37 publications
(42 reference statements)
2
8
0
Order By: Relevance
“… 37 , 48 Former research indicated that diseases induced by LPS in rat models are linked to abnormalities in hemodynamic parameters. 49 , 50 It has been documented that after treatment with LPS in rats, the HR and HWI are augmented, while LVEF and MAP are lessened, 37 , 38 which was consistent with our findings. We also confirmed that Dioscin reversed the effects of LPS on HR, HWI, LVEF, and MAP in SIC rats.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“… 37 , 48 Former research indicated that diseases induced by LPS in rat models are linked to abnormalities in hemodynamic parameters. 49 , 50 It has been documented that after treatment with LPS in rats, the HR and HWI are augmented, while LVEF and MAP are lessened, 37 , 38 which was consistent with our findings. We also confirmed that Dioscin reversed the effects of LPS on HR, HWI, LVEF, and MAP in SIC rats.…”
Section: Discussionsupporting
confidence: 92%
“…LPS, a major component of the outer membrane of Gram‐negative bacteria, is frequently used to induce SIC in rats as an important immunomodulator 37,48 . Former research indicated that diseases induced by LPS in rat models are linked to abnormalities in hemodynamic parameters 49,50 . It has been documented that after treatment with LPS in rats, the HR and HWI are augmented, while LVEF and MAP are lessened, 37,38 which was consistent with our findings.…”
Section: Discussionsupporting
confidence: 90%
“…Previous study showed that M. officinalis oligosaccharides can regulate mitochondrial autophagy in astrocytes. 21 Our results identified the inhibitory effect of another extract from M. officinalis How. on RANKL-induced OCP autophagy.…”
Section: Discussionmentioning
confidence: 59%
“…Inflammation and mitochondrial dysfunction are also associated with the pathogenesis of depression ( Bansal and Kuhad, 2016 ; Kohler et al, 2016 ). In addition, Morinda Officinalis Oligosaccharide Capsule mitigate depression by regulating Mitofusin two protein-mediated mitophagy in rats ( Yang et al, 2023 ). Morinda Officinalis Oligosaccharide Capsule mainly contains inulin-type oligosaccharides extracted from the roots of M. officinalis, which is effective in ameliorating symptoms of depressive disorder ( Zhang et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%